Morphological study of Schizaea Pectinata (L.) Sw. (Schizaeaceae) - Mwafongo, Elizabeth (Department of Biological Sciences, 2017)
Morphometrics was used to study variation in Schizeae pectinata as previous study showed that material originating from the summer rainfall area of South Africa differ in several aspects from that originating from the winter rainfall area. The plant has a simple structure and consequently spore, stoma and sporangia sizes, as well as the number per lamina was studied to determine if the species can be subdivided into two groups, e summer and e winter rainfall group, as was previously hypothesised. Univariate and bivariate methods were used to display the extent of variation within the species. Univariate analysis reﬂect variability of spore and stomata size, and the number of pinna pairs per lamina. Statistical analyses showed that interpopulation variation for these characters are often highly significant. Phonetic methods were used in the analyses of the data set and shows continuous variation in this species. This continuous variation in Schizaea pectinata could be linked to a phenotypic response to environmental differences between the two regions.